IR, PMR and Ligand Field Spectral Studies on Ti(III), Mn(III), Cr(III), Sb(III) and Bi(III) Complexes of Sulphur and Selenium Ligands - Pandey, R.N.; Kumar Singh, Rajnish; Shahi, Kalpana (Asian Journal of Chemistry, 2011)
Dibenzyl sulphide (DBS) and dibenzyl selenide (DBSe) form stable complexes with Ti(III), Mn(III), Cr(III), Sb(III) and Bi(III) ions having general formula [ML3Cl3] (M = Ti, Mn, Cr; L = DBS/DBSe), [ML2Cl3] (M = Sb and Bi) and [TiL2(Py)2Cl2]Cl. Ti(III), Cr(III) and Mn(III) forms mer-octahedral and Sb(III) and Bi(III) forms distorted octahedral structure in which one of the corners is occupied by inert pair. Bis-ligand [TiL2(Py)2Cl2]Cl complexes have trans position of ligand in octahedral structure. The IR, UV-vis and 1H NMR spectral data are in good agreement with assigned structure.